Pemberdayaan Masyarakat Melalui Eco-Printing Di Komunitas Kalingayahan, Filipina - Kurnianingsih, Marisa; Prakoso, Andria Luhur; Fairuzzaman, Fahmi; Salazar, Ramonita A; Iksan, Muchamad; Zuhdi, Syaifudin; Febriani, Hanifah (Abdimas Indonesian Journal, 2025)
This community service aims to empower the community through the introduction of eco-printing techniques in the Kalingayahan Community, Philippines. This community service is the result of an international collaboration between the Faculty of Law, Universitas Muhammadiyah Surakarta and Our Lady of Fatima University in the Philippines. Eco-printing, which uses natural materials such as leaves and flowers, supports environmental conservation and has economic potential through products of high aesthetic value. In a country rich in biodiversity like the Philippines, eco-printing can contribute to the creative economy while reducing environmental impacts. The method of this community service is through lectures and simulations. Community empowerment through eco-printing has received a positive response from both the community and the government in Kalingayahan, Philippines. Eco-printing crafts can support sustainable social, economic, and environmental change, while supporting global goals for sustainability and community empowerment by spreading Indonesian crafts.